Modelling the spray deposition and efficacy of two mineral oil-based products for the control of California red scale, Aonidiella aurantii (Maskell) - Garcerá, Cruz; Moltó, Enrique; Zarzo, Manuel; Chueca, Patricia (2017)
The pattern and quantity of pesticide deposition may affect the efficacy of pesticide treatments. In this study we evaluated under laboratory conditions the efficacy of two petroleum-derived spray oils (PDSO) (Laincoil (R), an nC21 oil with a content of 83% w/v, Oil A, and Sunspray Ultrafine (R), an nC21 with a content of 85% w/v, Oil B, both with an unsulfonated residue of 92%) applied at 1.5% concentration at five volumes (0.5, 1, 2, 3 and 4 ml) against different stages of Aonidiella aurantii Maskell (Homoptera: Diaspididae). In parallel, we characterized the deposition pattern of treatments resulting from these five volumes and two PDSOs. The objective was to model deposition characteristics and efficacy as a function of the deposited volume in order to determine the optimum volume per unit surface that should be applied to control this pest. Different models that depend on the developmental stage and relate to the efficacy of the treatment as a function of the deposited volume have been obtained for both PDSOs, thus providing a scientific basis for product efficacy comparison. Furthermore, our results are also relevant to find an adequate trade-off between sprayed pesticide volume and expected efficacy. (C) 2011 Elsevier Ltd. All rights reserved.